General speech intended for generality in the Qur’an through Ibn Hayyan’s interpretation (Al-Bahr Al-Muhit): a critical and analytical study - Mahmoud Sanad Almuslim,; Omar Abdullah Al Anbar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Holy Qur’an is characterized by a variety of discourses, including the general discourse intended for the general public. And that the discourse as a whole represents the big tent under which all the other aspects of the discourse enter. And that there is a mutualistic relationship between the aspects of the discourse and the methods in which they were mentioned. When the discourse comes in an interrogative style, for example, we find that it either states a specific fact and its purpose is confirmation, or denies an act and is outside to reprimand.، The general discourse was contained in various rhetorical methods, such as the required construction methods, including: the appeal, the command, the prohibition, and the question, as well as the conditional sentence, and the general discourse intended by the general in the style of the palace also and others. This feature is general in all other aspects of discourse, as the phenomena of semantics are the main pillar in the verses of discourse, so no single verse of the discourse can be found without a phenomenon of semantics that has topped it.